Building and validation of wireframe for software prototype aimed at occupational vaccines - Hahn, Joice Rodrigues Machado; Schröder, Melanie; Antoniolli, Silvana Aline Cordeiro; Bueno, Elizete Maria de Souza; Souza, Luccas Melo de; Paz, Adriana Aparecida (Acta Scientiarum. Health Sciences, 2025)
To build and validate the functionality and interface of the wireframe of a software prototype for managing worker vaccinations. Study of technological production, based on User-Centered Design (UCD) and Scrum framework, with an exploratory and descriptive design using a quantitative approach. Study approved by the Research Ethics Committee (Opinion number 5.040.951/2021). The wireframe modeling of the software prototype was built in Bizagi Modeler® and validated by experts. The functionality and interface were considered satisfactory at 92% to 100%, respectively. The items with the lowest agreement were related to contraindications and information about vaccination coverage being in a place that was easy to view and understand, which reached a CI of 0.83. In the global validation of the wireframe, the experts’ agreement reached a CI of 96%. The building of the wireframe took into account end user interaction. The validation of the software prototype wireframe provides an excellent CI result, which was achieved in all of its evaluated items. The software is able to optimize nurses’ time in the management and control of vaccines in occupational health services, which contributes to increasing workers’ vaccination coverage and protecting the community.